2012
DOI: 10.1007/s11418-012-0670-y
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of D-002, a mixture of beeswax alcohols, against indomethacin-induced gastric ulcers and mechanism of action

Abstract: D-002, a mixture of higher aliphatic beeswax alcohols, produces gastroprotective and antioxidant effects. To investigate the gastroprotective effect of D-002 against indomethacin-induced ulcers, oxidative variables and myeloperoxidase (MPO) activity in the rat gastric mucosa were examined. Rats were randomized into six groups: a negative vehicle control and five indomethacin (50 mg/kg) treated groups, comprising a positive control, three groups treated orally with D-002 (5, 25 and 100 mg/kg) and one group with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 39 publications
1
27
0
1
Order By: Relevance
“…It was reported that the oxidative stress in gastric tissue causes damage to key biomolecules such as lipids. In conjunction with the report of [64][65][66], the present study recorded elevations in the levels of the end products of lipid peroxidation, malondialdehyde (MDA) in the gastric tissues following SGU. The elevation in MDA suggests enhanced lipid peroxidation leading to tissue damage and failure of antioxidant defense mechanisms to prevent the formation of excessive free radicals.…”
Section: Discussionsupporting
confidence: 81%
“…It was reported that the oxidative stress in gastric tissue causes damage to key biomolecules such as lipids. In conjunction with the report of [64][65][66], the present study recorded elevations in the levels of the end products of lipid peroxidation, malondialdehyde (MDA) in the gastric tissues following SGU. The elevation in MDA suggests enhanced lipid peroxidation leading to tissue damage and failure of antioxidant defense mechanisms to prevent the formation of excessive free radicals.…”
Section: Discussionsupporting
confidence: 81%
“…The effect of D-002 200 and 400 mg/kg on leukocyte infiltration was greater than that OMP 20 mg/kg, but since only one dose of OMP was tested we cannot conclude that D-002 was more effective than OMP on such regard. These results should not be surprising since both D-002 [24] and OMP [35] have shown to produce anti-inflammatory effects on the gastric mucosa.…”
Section: Discussionmentioning
confidence: 77%
“…Nevertheless, in light of the role of the oxidative damage are critical in pathogenesis of RE [36] the antioxidant effects of D-002 [23,24,27] may contribute to the present results. In such regard, previous studies have demonstrated that the efficacy of D-002 for preventing indomethacin-induced gastric ulcers in rats was associated to the reduction of lipid peroxidation, [23,24] protein oxidation, generation of hydroxyl radical and to the increase of superoxide dismutase and glutathione peroxidase enzyme activities in gastric mucosa.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations